]]>
LearnNext
Get a free home demo of LearnNext

Available for CBSE, ICSE and State Board syllabus.
Call our LearnNext Expert on 1800 419 1234 (tollfree)
OR submit details below for a call back

clear

Bayes' Theorem

9,473 Views
Have a doubt? Clear it now.
live_help Have a doubt, Ask our Expert Ask Now
format_list_bulleted Take this Lesson Test Start Test

Bayes' Theorem - Lesson Summary

The set of events E1, E2, E3, ..., En represents a partition of sample space S, if:

• Ei ∩ Ej = ∅, i ≠ j , i, j = 1,2,3,...,n

• E1 ∩ E2 ∩ E3 ∩...∩ En = S P(Ei) > 0 ∀ i = 1,2,3,...,n

Theorem of Total Probability:

Let {E1, E2, ... En} be a partition of sample space S, and suppose that each of the events E1, E2, ... En has non-zero probability of occurrence. Let A be any event associatedwith S.Then
P(A) = P(E1)P(A|E1) + P(E2)P(A|E2) + ... + P(En)P(A|En)

= ∑j=1n P(Ej)P(A|Ej)

Proof:

{E1, E2, ..., En} is a partition of sample space S.

∴ S = E1∩ E2∩ ... ∩ En

Ei∪Ej = f, ij and i, j = 1, 2, 3, ..., n

P (Ei) > 0 ∀ i = 1,2, 3, ..., n

For any event A associated with S, A = A ∩ S

= A ∩ (E1∪ E2∪ ... ∪ En) [∵ S = E1∪ E2∪ ... ∪ En]

= (A ∩E1) ∪(A ∩E2) ∪ ... ∪(A ∩En)

A ∩Eiis a subset of Eiand A ∩Ejis a subset of Ej.

Given, Ei and Ej are disjoint for ij.

∴ A ∩Ei and A ∩Ej are also disjoint ∀ij and i, j = 1, 2, 3, ..., n.

Thus, P(A) = P[(A ∩E1) ∪(A ∩E2) ∪ ... ∪(A ∩En)]

= P(A ∩E1) + P(A ∩E2) + ... + P(A ∩En)

By the multiplication rule of probability,

P(A) = P(E1)P(A|E1) + P(E2)P(A|E2) + ... + P(En)P(A|En)

P(A) = ∑j=1n P(Ej)P(A|Ej)

Bayes' Theorem: If E1, E2, ..., En are n non empty events that constitute a partition of sample space S, i.e. E1, E2, ..., En are pair-wise disjoint and E1∪E2∪...∪En = S, and A is any event of non-zero probability, then


P(Ei|A) = P(Ei)P(A|Ei) / ∑j=1n P(Ej)P(A|Ej) ∀ i = 1,2,3,......,n

Proof:

Given, E1, E2, ..., En is a partition of sample space S.

⇒ E1, E2, ..., En are pair-wise disjoint

E1∪ E2∪... ∪ En = S

By the formula of conditional probability,

P(Ei|A) = P(A∩Ei)/P(A)

= P(Ei)P(A|Ei) / P(A) [∵ P(A∩Ei) = P(Ei)P(A|Ei)]

= P(Ei)P(A|Ei) / ∑j=1n P(Ej)P(A|Ej) [∵ P(A) = ∑j=1n P(Ej)P(A|Ej)]

P(Ei|A) = P(Ei)P(A|Ei) / ∑j=1n P(Ej)P(A|Ej) ∀ i = 1,2,3,...., n

Hence it is proved.

Sometimes, Bayes' theorem is called the formula for the probability of causes. Events E1, E2, ..., En are called hypotheses. P(Ei) is called the priori probability of the hypothesis, Ei.

The conditional probability, P(Ei|A), is called the posteriori probability of the hypothesis, Ei.

Comments(0)

Feel the LearnNext Experience on App

Download app, watch sample animated video lessons and get a free trial.

Desktop Download Now
Tablet
Mobile
Try LearnNext at home

Get a free home demo. Book an appointment now!

GET DEMO AT HOME